A comparison of the effect of supplementation and sunlight exposure on serum vitamin D and parathyroid hormone: A systematic review and meta-analysis. Issue 11 (16th June 2020) - Moradi, Sajjad; Shahdadian, Farnaz; Mohammadi, Hamed; Rouhani, Mohammad Hossein
Abstract: Background: Supplementation and getting sunlight exposure are two treatments for vitamin D deficiency. However, studies reported conteroversial findings regarding the efficacy of these two methods. Objective: To compare the effect of oral vitamin D supplementation with sunlight exposure on serum vitamin D and parathyroid hormone (PTH). Methods: A computer-based literature search through PubMed, Scopus and Google scholar search engines was conducted until April 2019 to find clinical trials which compared the effect of oral vitamin D supplementation with sunlight exposure on serum vitamin D and PTH. Means for serum 25-hydroxy vitamin D3 (25(OH) D3) and PTH concentration were extracted. A subgroup analysis was used to detect potential sources of inter-study heterogeneity. Mean differences (MD) were analyzed using a random-effects model (the DerSimonian-Laird approach). Results: A total of seven papers were included in the meta-analysis. Pooled analysis showed that vitamin D supplementation significantly elevated levels of serum 25(OH) D3 in comparison with sunlight exposure (MD: 8.56nmol/l, 95%CI: 4.15, 12.97, T 2 = 40.32%, H 2 = 9.45%, P for heterogeneity p < 0.001). Also, the difference between the effect of vitamin D supplementation and sun exposure was lower in studies which used UVB radiation compared with studies which applied direct sunlight (MD: 11.65 nmol/l, 95%CI: 7.02, 16.28; P for between subgroup heterogeneity = 0.001). Conclusion: Vitamin D supplementation was more effective than sun exposure at increasing serum 25(OH) D3. The difference between efficacy of vitamin D supplementation and sun exposure was lower in studies which used long-term sun exposure or applied UVB treatment instead of direct sunlight.